Realising local government visions for developing district heating: Experiences from a learning country. (November 2016) - Bush, Ruth E.; Bale, Catherine S.E.; Taylor, Peter G.
Abstract: District heating (DH) has an important role to play in enabling cities to transition to low-carbon heating. Although schemes are commonplace in some countries, in 'learning countries' where building-level technologies make up the majority of heating systems there are numerous barriers to introducing DH. Local governments are seen as key actors in helping to create a 'shared vision' for DH amongst stakeholders. This study uses interviews with stakeholders from a range of sectors in the UK (an example of a learning country) to examine the visions of local actors for developing DH and the types of national policy that would support local implementation of these visions. The analysis shows that in engaging with DH development local governments seek multiple types of value. Realising this value will most likely happen by taking a long-term, planned approach to development. In contrast, national government policy is geared towards techno-economic criteria and may lead to only a minority of potential sites being developed, without realisation of wider social or environmental benefits aligned to local visions. The work highlights the importance of local strategic planning, enabled by aligned national policy, in realising the full economic, environmental and social benefits of DH. Highlights: Local governments are key to the development of district heating (DH). Local government-led visions of DH seek to deliver complex value. In the UK development is led by funding and commercial factors and is not strategic. To enable DH, national policy must align with the vision of local actors. Social and environmental criteria must be incorporated in decision-making.